Analysis of the biological activity of the phenazine complex of Pseudomonas chlororaphis subsp. aurantiaca in relation to normal and malignant cell lines - Veremeenko, Ekatsiaryna G.; Liavonchyk, Katerina V.; Maximova, Natalia P. (Experimental Biology and Biotechnology, 2018)
In the course of the experiment, water-soluble and fat-soluble fractions of phenazine antibiotics from the P. chlororaphis subsp. aurantiaca B-162 and derived on its basis producer strains capable of overproducing phenazines were obtained and analyzed. Analysis of the cytotoxic and cytostatic activity of isolated water-soluble phenazine complexes shows that malignant cells show much greater sensitivity to these compounds, compared to normal cells. In support of this, a microscopic analysis of samples of cultures of malignant and normal cells, subjected to treatment with various fractions of phenazine antibiotics isolated from the strains studied, was carried out. He showed that on the second day of cultivation in cultures of malignant lines, a large number of cells (from 7 to 96 %) died by apoptosis, less often necrosis, whereas in a culture of fibroblasts such a massive cytotoxic effect was not found. The cytotoxicity of liposoluble fractions is extremely high for all cell cultures studied, which may be due to the presence of DMSO and its ability to enhance the cytotoxic properties of phenazines.
Keywords: solid-phase extraction; phenazine; mouse fibroblasts; cytotoxic activity; HeLa; MCF-7; Pseudomonas chlororaphis subsp. aurantiaca B-162